2013
DOI: 10.1175/mwr-d-13-00003.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of SSMIS Upper Atmosphere Sounding Channels for High-Altitude Data Assimilation

Abstract: Upper atmosphere sounding (UAS) channels of the Special Sensor Microwave Imager/Sounder (SSMIS) were assimilated using a high-altitude version of the Navy Global Environmental Model (NAVGEM) in order to investigate their potential for operational forecasting from the surface to the mesospause. UAS radiances were assimilated into NAVGEM using the new Community Radiative Transfer Model (CRTM) that accounts for Zeeman line splitting by geomagnetic fields. UAS radiance data from April 2010 to March 2011 are shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 57 publications
5
42
0
Order By: Relevance
“…Between 10 and 0.1 hPa, comparative spectral analyses confirm the lack of variability on shorter time scales (up to 20 days and in the order of~10 dB at 5 day period) that is neither present in ECMWF and MERRA products nor in the free-running MPI-ESM-LR climate model. These results are in line with a recent study by Hoppel et al [2013], who showed that assimilation of microwave imager/sounder data could provide reliable large-scale constraints throughout the mesosphere for operational high-altitude analysis.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Between 10 and 0.1 hPa, comparative spectral analyses confirm the lack of variability on shorter time scales (up to 20 days and in the order of~10 dB at 5 day period) that is neither present in ECMWF and MERRA products nor in the free-running MPI-ESM-LR climate model. These results are in line with a recent study by Hoppel et al [2013], who showed that assimilation of microwave imager/sounder data could provide reliable large-scale constraints throughout the mesosphere for operational high-altitude analysis.…”
Section: Discussionsupporting
confidence: 92%
“…The MLT is a dynamic medium with variability over time scales ranging from minutes to days. Both the mean state and the variability within the MLT are subject to inaccuracies both in current operational analyses and reanalyses [Rienecker et al, 2011;Hoppel et al, 2013]. troposphere and lower stratosphere (i.e., below~35 km) because their weighting function peaks are generally in those regions [Hoppel et al, 2013].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These measurements were used to validate a fast model developed from the radiative transfer model of Rosenkranz and Staelin (1988). Moreover, the measurements were also used together with data from the Microwave Limb Sounder (MLS) on board the Aura spacecraft for assimilation in a numerical weather prediction (NWP) model (Hoppel et al, 2013). Schwartz et al (2006) also reported a comparison of another radiative transfer model with measurements of the 118 GHz oxygen line from MLS.…”
Section: F Navas-guzmán Et Al: Zeeman Effect Measurements In Atmospmentioning
confidence: 99%